THE MAIN DIRECTIONS OF ARTICLES ON THE HISTORY OF THE KOKAND KHANATE IN THE “TURKISTAN COLLECTION” - Usmonov Abdullajon (International Engineering Journal For Research & Development, 2021)
The article describes the main directions and descriptions of articles on the history of the Kokand Khanate in the “Turkistan Collection”. The article was written from the point of view of historiography and source studies.